Influence of Zn(NO3)2 concentration during the ZnO electrodeposition on TiO2 nanosponges used in photoelectrochemical applications. Issue 10 (15th May 2022) - Navarro-Gázquez, P.J.; Blasco-Tamarit, E.; Muñoz-Portero, M.J.; Solsona, B.; Fernández-Domene, R.M.; Sánchez-Tovar, R.; García-Antón, J.
Abstract: TiO2 /ZnO hybrid nanostructures were formed by electrochemical anodization of titanium and subsequently ZnO electrodeposition. Different Zn(NO3 )2 concentrations were used for electrodeposition (10–60 mM). A structural, morphological, and compositional characterisation was performed using FE-SEM, TEM, AFM, XRD, UV–Visible spectroscopy, and band gap measurements. It was reported that the morphology of the nanostructures changed with the Zn(NO3 )2 concentration. Nanosponges were observed for concentrations from 10 mM to 30 mM whereas at 40 mM the morphology changed to well-defined ZnO hexagonal nanorods. At 50 mM a surface covered by ZnO with undefined rods could be seen and, at 60 mM, a morphology of nanoplatelets was observed. Besides, as Zn(NO3 )2 concentration increased, the ZnO amount, the roughness, and the ZnO crystalline size also increased, while the band gap decreased. Electrochemical characterisation of nanostructures was performed by water splitting, stability to photocorrosion, EIS, and Mott-Schottky tests. The optimal samples were TiO2 /ZnO hybrid nanostructures electrodeposited with 30 mM Zn(NO3 )2, since they were stable against photocorrosion and, compared to TiO2 nanosponges, showed an increase in photoelectrochemical activity of 204%, a lower resistance to charge transfer, and a higher donor density. Overall, the most efficient samples presented an intermediate Zn-loading because of a maximization of the TiO2 –ZnO interaction and the prevention of the formation of non-interacting ZnO structures.